It is: 6*(5-2)+6 = 24.
To make 6 6 2 9 equal 24, you can use the following equation: 6 ÷ (1 - (2 ÷ 9)) = 24. This equation involves using the division operation and parentheses to manipulate the numbers in a specific order to achieve the desired result of 24.
6(7 - (2 + 1)) = 24 2 plus 1 equals 3. 7 minus 3 equals 4. 4 times 6 equals 24.
9C2 - 6*2 = 36 - 12 = 24
6X2-6x4=24
It is: 6*(5-2)+6 = 24.
2*(6/6 + 11) = 2*(1 + 11) = 2*12 = 24. Simple!
To make 6 6 2 9 equal 24, you can use the following equation: 6 ÷ (1 - (2 ÷ 9)) = 24. This equation involves using the division operation and parentheses to manipulate the numbers in a specific order to achieve the desired result of 24.
add 2+5+6+6+2+4 which equals 24.but you get the 2 and 4 from the 24 that's in the problem.
9C2 - 6*2 = 36 - 12 = 24
6(7 - (2 + 1)) = 24 2 plus 1 equals 3. 7 minus 3 equals 4. 4 times 6 equals 24.
6 × (5 + 2 - √9) = 24.
6X2-6x4=24
54 divided by 3 is equal to 18. 18+6 is equal to 24.
2 eighths of 24 is 2/8 multiplied by 24 that is equal to 6
[(-6) - (-9)*2]*2 = [-6 + 18]*2 = 12*2 = 24. Simple!
How can 2,2,6,9 solve to 24